Government accounting in Australia; a book of readings - Mathews, Russell L.; Jay, W. R. C. (Melbourne: Canberra: F. W. Cheshire, 1968)
The book intends to provide selection of what has been written in Australia and indicate the scope for further development in government accounting.
Bibliography: p. 286-288.
gp. 22/01/2019
loan
Keywords: Finance, Public